The Physical and Moral Impact of Tourism Activities on School-Age Children: A Case Study in Karshi City - Mansur, Yodgorov (Jurnal Teknologi Pendidikan, 2025)
This article examines the physical and moral impact of tourism activities on school-age children, with a particular focus on the city of Qarshi. The study analyzes how educational tourism, recreational trips, cultural excursions, and sports-related travel influence children’s physical development, emotional well-being, social interaction skills, and moral values. Special attention is given to the role of tourism in shaping children's worldview, enhancing their civic responsibility, promoting healthy lifestyles, and strengthening their cultural awareness. The findings highlight both the positive outcomes and potential challenges associated with involving school-aged children in tourism activities, offering recommendations for creating safe, value-oriented, and pedagogically meaningful tourism programs.